2006
DOI: 10.2119/2005-00034.ueda
|View full text |Cite
|
Sign up to set email alerts
|

Oral Adsorbent AST-120 Decreases Serum Levels of AGEs in Patients with Chronic Renal Failure

Abstract: Advanced glycation end products (AGEs) are senescent macroprotein derivatives that are formed at an accelerated rate in patients with chronic renal failure (CRF). AGE formation and accumulation in plasma and vascular tissues contribute to accelerated atherosclerosis in this devastating disorder. AST-120 is an oral adsorbent that attenuates the progression of CRF by removing uremic toxins. Recently, AST-120 has been reported to reduce the progression of atherosclerosis as well. However, whether AST-120 decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 25 publications
0
57
0
Order By: Relevance
“…Since AGEs represent an important class of uremic toxins and that, as described above, diet-derived AGEs could play an important role in atherogenesis, we investigated whether Kremezin R treatment could decrease serum levels of AGEs in non-diabetic CRF patients. Administration of Kremezin R (6 g/day) for 3 months significantly decreased serum levels of AGEs in non-diabetic CRF patients, whereas AGE levels remained unchanged in age-and renal function-matched CRF patients without Kremezin R [44]. In addition, patient serum after Kremezin R treatment significantly reduced mRNA levels of RAGE, MCP-1, and VCAM-1 in HUVEC compared with serum before treatment.…”
Section: (2) Renal Injurymentioning
confidence: 91%
“…Since AGEs represent an important class of uremic toxins and that, as described above, diet-derived AGEs could play an important role in atherogenesis, we investigated whether Kremezin R treatment could decrease serum levels of AGEs in non-diabetic CRF patients. Administration of Kremezin R (6 g/day) for 3 months significantly decreased serum levels of AGEs in non-diabetic CRF patients, whereas AGE levels remained unchanged in age-and renal function-matched CRF patients without Kremezin R [44]. In addition, patient serum after Kremezin R treatment significantly reduced mRNA levels of RAGE, MCP-1, and VCAM-1 in HUVEC compared with serum before treatment.…”
Section: (2) Renal Injurymentioning
confidence: 91%
“…The oral adsorbent AST-120 could be an interesting alternative means of lowering uremic toxin levels. It reduces intestinal absorption of IS (127) and decreases AGEs levels in non diabetic CKD patients (128). In uremic rats, it lowers the serum concentration of IS and reduces kidney fibrosis and progression of CKD (129).…”
Section: Drugsmentioning
confidence: 99%
“…We have recently found that administration of AST‐120 (Kremezin) (6 g/day) for three months significantly decreases the serum level of AGEs in non‐diabetic CRF patients, whereas AGE levels remain unchanged in age‐ and renal function‐matched CRF patients without AST‐120 (26). In addition, patient serum after AST‐120 treatment significantly reduced mRNA levels of RAGE, MCP‐1, and VCAM‐1 in endothelial cells compared with serum before treatment.…”
Section: Food‐derived Ages and Vascular Complications In Diabetes: Ormentioning
confidence: 99%